Advances in understanding the fundamental aspects required for successful cryopreservation of Australian flora - Funnekotter, Bryn; Mancera, Ricardo; Bunn, E. (Springer, 2017)
Australia is host to an amazing diversity of species, many of which require conservation efforts. In vitro culture provides a tool for not only conserving these threatened species but allows for their propagation from limited starting material. Cryopreservation provides the greatest long-term storage option for in vitro cultures and as a conservation tool for other germplasm. However, while cryopreservation has proven capable of delivering viable long-term storage with some plant taxa, the process of deriving protocols is still largely an incremental process. The key to faster and more intuitive optimising of cryopreservation protocols lies with continuing to develop a better understanding of key factors, including issues with plant physiology (such as genetic stability, the composition of the proteome and metabolome, cell membrane characteristics, and antioxidant defences) and how the stresses imposed by cryopreservation (such as the excision damage, desiccation, cryoprotective agent toxicity, ice crystal damage, and cooling to cryogenic temperatures) interact and contribute to the cryocapability of a species. This review focuses on the advances that have been made towards understanding cryogenic stress and how this has led to improved cryopreservation protocols, in the context of cryopreserving Australian flora.